Revitalisasi UMKM Kabupaten Langkat: Penguatan Mitra Pendamping dengan Marketing Agility dan Inovasi Keuangan: Pengabdian - Onan Marakali Siregar; Kartini Harahap (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Partnership Service Program aims to revitalize MSMEs in Langkat Regency by strengthening mentoring partners, with a focus on marketing agility and financial innovation. MSMEs in Langkat Regency face various challenges, such as limited market access, low product innovation, and difficulty accessing finance. Furthermore, the capacity of mentoring partners to provide support is also suboptimal. This program offers solutions through intensive training and mentoring to mentoring partners, which will then help MSMEs adopt digital marketing strategies, improve financial literacy, and access innovative financing sources. The program consists of three main stages: preparation, implementation, and evaluation. The preparation stage includes identifying needs, developing training materials, and coordinating with stakeholders. The implementation stage includes training mentoring partners, mentoring MSMEs, and implementing digital marketing strategies and financial innovation. The evaluation stage is conducted to monitor and evaluate the program's success and provide feedback for improvement. This program is expected to increase the competitiveness and sustainability of MSMEs in Langkat Regency, while simultaneously promoting inclusive local economic growth. Furthermore, this program also contributes to the achievement of higher education Key Performance Indicators (KPIs), such as student experiences outside campus, lecturers' off-campus activities, and community utilization of lecturers' work.